Pengabdian Kepada Masyarakat Melalui Edukasi Pengelolahan Sampah Menjadi Nilai Ekonomis di RW 13 Bekasi - Anita Sriwaty Pardede; Minar Gultom; Kristina Sinuraya (Jurnal Pengabdian Ilmu Kesehatan, 2026)
Waste is the residue of human activities or materials that are no longer used and are discarded. In various countries, especially in Indonesia, the waste problem remains a major issue that is difficult to resolve because people are not yet aware of the dangers that can be caused by waste. Plastic waste can be created into various handicrafts such as tissue holders, cup holders, accessories and other home decorations. The purpose of this activity is to increase the community's knowledge and skills in managing plastic waste in the home and surrounding environment. This goal is achieved through the implementation of socialization of plastic waste utilization involving housewives from the Family Empowerment and Welfare Group (PKK) to teach how to process the waste. This activity is taught using the reuse method, where waste found in the home and the surrounding environment is reprocessed into products that are useful and have economic value. Participants in the socialization are taught to process waste into various handicrafts such as wall hangings, flower vases, bags, wallets, etc. These crafts can be used at home and can be sold, the proceeds of which can be used to support the PKK activities themselves, including for purchasing consumption activities carried out by the PKK Group. This activity successfully increased the knowledge of the participants, as evidenced by the results of a questionnaire distributed to show that 85% of participants had a very good understanding of the handicraft making techniques taught. This activity was integrated into Family Welfare Movement (PKK) activities to support the skills of housewives and future community empowerment.